The Influence of Brand Equity, Life Style, and Product Variety on Purchase Decisions for Aerostreet Shoes - Rianto, Taufik; Hakimah, Ema Nurzainul (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim : Aims to determine the influence of brand equity, life style, product variations both partially and simultaneously on the decision to purchase Aerostreet shoes. Design/Methode/Approach : The purpose of this study was to examine the influence of product variations, lifestyle factors, and brand equity on decisions to buy Aerostreet shoes. This study is cause-and-effect in nature and employs a quantitative methodology. The population in this study refers to all Aerostreet product users, regardless of how many there are in the count. Using random sampling techniques, a sample of 40 respondents was selected for analysis. Multiple linear regression is used in this study to determine the degree to which the independent variable affects the dependent variable. Research Finding : This research shows that brand equity, life style, and product variety have a significant influence on the decision to purchase Aerosreet brand shoes in generation z.. Theoretical contribution/Originality : Brand equity is the identity of a product that can be trusted to influence consumer behavior and purchasing decisions. Measuring the impact and preferences of consumers on life style, and digging deeper into product variations from a consumer perspective influences purchases. Practitionel/Policy implication : This research provides practical implications for Aerostreet Shoes in improving purchasing decisions. Research limitation : This research only discusses brand equity, life style, and product variety as independent variables. There are still other variables that influence the dependent variable that need to be researched further.